Posterior Segment Ophthalmic Drug Delivery: Role of Muco-Adhesion with a Special Focus on Chitosan - Ayah Mohammad Burhan; Butsabarat Klahan; Wayne Cummins; Vanessa Andrés-Guerrero; Mark E. Byrne; Niall J. O'Reilly; Anuj Chauhan; Laurence Fitzhenry; Helen Hughes (MDPI AG, 2021)
Posterior segment eye diseases (PSEDs) including age macular degeneration (AMD) and diabetic retinopathy (DR) are amongst the major causes of irreversible blindness worldwide. Due to the numerous barriers encountered, highly invasive intravitreal (IVT) injections represent the primary route to deliver drugs to the posterior eye tissues. Thus, the potential of a more patient friendly topical route has been widely investigated. Mucoadhesive formulations can decrease precorneal clearance while prolonging precorneal residence. Thus, they are expected to enhance the chances of adherence to corneal and conjunctival surfaces and as such, enable increased delivery to the posterior eye segment. Among the mucoadhesive polymers available, chitosan is the most widely explored due to its outstanding mucoadhesive characteristics. In this review, the major PSEDs, their treatments, barriers to topical delivery, and routes of topical drug absorption to the posterior eye are presented. To enable the successful design of mucoadhesive ophthalmic drug delivery systems (DDSs), an overview of mucoadhesion, its theory, characterization, and considerations for ocular mucoadhesion is given. Furthermore, chitosan-based DDs that have been explored to promote topical drug delivery to the posterior eye segment are reviewed. Finally, challenges of successful preclinical to clinical translation of these DDSs for posterior eye drug delivery are discussed.